Features of technical and tactical actions of highly skilled athletes when swimming a distance of 100 meters by front crawl - Olga Pilipko (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to determine the features of technical and tactical actions of highly skilled athletes when swimming a distance of 100 meters by front crawl. Material & Methods: analysis and generalization of literary sources, video filming, timekeeping, methods of mathematical statistics. The contingent of subjects consisted of athletes who specialized in a distance of 100 meters in the way of swimming the front crawl and had the level of sports qualification master of sports of Ukraine, master of sports of international grade. Results: dynamics of indicators of technical and tactical skill among highly skilled athletes during their overcoming the 100 meter distance by front crawl has been investigated; characterized by the variability of technical and tactical actions of highly skilled athletes in different parts of the competition distance of 100 meters; determined the degree of influence of speed, pace and "step" of the cycle of rowing movements on the result of swimming a distance of 100 meters using the front crawl. Conclusion: overcoming the distance of 100 meters by the front crawl has its own specifics, which is reflected in changes in the indicators of technical and tactical masterhood; model characteristics of the most influential parameters of technical and tactical actions of highly skilled swimmers can serve as a guideline for improving the training process of athletes depending on their distance specialization.